2021
DOI: 10.1111/ene.15040
|View full text |Cite
|
Sign up to set email alerts
|

Headache as an acute and post‐COVID‐19 symptom in COVID‐19 survivors: A meta‐analysis of the current literature

Abstract: Background Headache is identified as a common post‐COVID sequela experienced by COVID‐19 survivors. The aim of this pooled analysis was to synthesize the prevalence of post‐COVID headache in hospitalized and non‐hospitalized patients recovering from SARS‐CoV‐2 infection. Methods MEDLINE, CINAHL, PubMed, EMBASE, and Web of Science databases, as well as medRxiv and bioRxiv preprint servers, were searched up to 31 May 2021. Studies or preprints providing data on post‐COVID headache were included. The methodologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
110
0
15

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(130 citation statements)
references
References 14 publications
5
110
0
15
Order By: Relevance
“…In another study carried out in Spain that included both in-patients and out-patients, headache was the symptom that most bothered 15.6% of patients [ 19 ]. A recent systematic review found a prevalence of headache in the acute phase of COVID-19 of 47.1% (95%CI: 35.8–58.6%) of patients, which is similar to our findings [ 20 ].…”
Section: Discussionsupporting
confidence: 92%
“…In another study carried out in Spain that included both in-patients and out-patients, headache was the symptom that most bothered 15.6% of patients [ 19 ]. A recent systematic review found a prevalence of headache in the acute phase of COVID-19 of 47.1% (95%CI: 35.8–58.6%) of patients, which is similar to our findings [ 20 ].…”
Section: Discussionsupporting
confidence: 92%
“…The symptoms of COVID-19 patients are varied, with the most common being fever, cough, digestive tract symptoms, sleep disorders and headaches, which are often treated by medication (Guan et al, 2020a;Bhat and Chokroverty, 2021;Fernández-De-Las-Peñas et al, 2021). Ibuprofen and acetaminophen are the most commonly used antipyretics.…”
Section: Symptomatic and Supportive Treatmentmentioning
confidence: 99%
“…In this issue, Fernandes‐de‐las‐Penas et al [ 2 ] confirm that headache is not only frequent in the acute phase of SARS‐CoV‐2 infection but is a notable COVID‐19 sequela in a subgroup of patients. Their findings are based on a meta‐analysis of various scientific databases up to May 2021, which involved 28,438 COVID‐19 survivors from 35 studies (longitudinal design in 40%).…”
mentioning
confidence: 99%
“…The world has been kept in suspense since early 2020 by coronavirus disease 2019 (COVID-19), a multi-organ disease caused by the highly contagious severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2). Cephalalgia, the most frequent early symptom of COVID-19, not only is painful but is a disabling condition that causes substantial personal suffering, impaired quality of life, and economic burden [1]. Headache in acute viral illness is seen as a consequence of the immune response, whereas the mechanism of action leading to its persistence thereafter is not well understood.…”
mentioning
confidence: 99%
See 1 more Smart Citation